2021
DOI: 10.1111/eth.13249
|View full text |Cite
|
Sign up to set email alerts
|

Field studies need to report essential information on social organisation – independent of the study focus

Abstract: Comparative studies on social evolution are ideally based on large datasets to ensure high statistical power, but their scientific validity also relies on the quality of the data. However, even though social organization, i.e., the composition of social units, is measured in many field studies testing specific hypotheses, these data are often not adequately reported. Here, 2 we summarise which data on social organization should always be reported regardless of the study focus to make them available for compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Recently, Makuya et al [111] highlighted that social organization data are often not fully or clearly reported in the published literature, ultimately hampering advances in our understanding of the evolution of sociality. For kinship composition specifically, it is important that, when possible, future studies report their pedigree data together with demographic data, such as the identity, age and sex of members of the same social unit, in line with the FAIR science principles [20,111]. Comparative research crucially relies on data shared in an open and standardized way [20,111].…”
Section: Canis Lupusmentioning
confidence: 99%
“…Recently, Makuya et al [111] highlighted that social organization data are often not fully or clearly reported in the published literature, ultimately hampering advances in our understanding of the evolution of sociality. For kinship composition specifically, it is important that, when possible, future studies report their pedigree data together with demographic data, such as the identity, age and sex of members of the same social unit, in line with the FAIR science principles [20,111]. Comparative research crucially relies on data shared in an open and standardized way [20,111].…”
Section: Canis Lupusmentioning
confidence: 99%
“…We believe that overgeneralizations, like assuming that most species of a taxon are solitary living, can lead to conclusions that are in contrast with the existing data [11] which might then bias comparative studies [50]. In sum, we need more field studies [50] that report data in a way they can be used in comparative analyses [27].…”
Section: Discussionmentioning
confidence: 99%
“…This is why intra-specific variation is important for understanding social evolution. Unfortunately, many papers we found failed to present their field data in a way that they could be included into our database [27]. Often no data but only a general statement about the assumed main form of social organization was reported, especially in mainly solitary species such as the Tasmanian devil or the koala.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the forms of social organization present in each population, we recorded the adult sex composition of all social units in a population using the classical definitions from Kappeler and van Schaik (8) and adding "sex specific group" as an additional category (Table S1). Studies that did not report the sex of individuals were not taken into account, following (30).…”
Section: Methodsmentioning
confidence: 99%